2021
DOI: 10.1080/0267257x.2021.1897650
|View full text |Cite
|
Sign up to set email alerts
|

Connecting consumers to producers to foster sustainable consumption in international coffee supply – a marketing intervention study

Abstract: Creating connections between consumers and producers (relational proximity) seems a promising approach to foster sustainable consumption behaviour in international food supply. In this intervention study, we tested three experiential marketing interventions to connect consumers to producers of an international communitysupported agriculture (CSA) partnership for coffee (Teikei Coffee). Consumers (N = 136), recruited at a fair for sustainable products and lifestyles in Germany, (a) watched a promotional video a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
0
8
0
2
Order By: Relevance
“…This single-case exemplar of Folgers 1850 coffee reveals that for ecologically embedded CE as part of the supply chain, there needs to be a consideration of the relationships among supply chain actors and the environment (both natural and business). Relationships are supported both by financial considerations (economic sustainability) through the sharing of benefits among all supply chain actors [49] and for sustainable consumption behaviour through the creation of connections between consumers and producers [101]. Blockchain enabled these relationships, but the single-case exemplar demonstrates that blockchain has not been utilized to its fullest potential.…”
Section: Discussionmentioning
confidence: 99%
“…This single-case exemplar of Folgers 1850 coffee reveals that for ecologically embedded CE as part of the supply chain, there needs to be a consideration of the relationships among supply chain actors and the environment (both natural and business). Relationships are supported both by financial considerations (economic sustainability) through the sharing of benefits among all supply chain actors [49] and for sustainable consumption behaviour through the creation of connections between consumers and producers [101]. Blockchain enabled these relationships, but the single-case exemplar demonstrates that blockchain has not been utilized to its fullest potential.…”
Section: Discussionmentioning
confidence: 99%
“…The government should implement more favorable policies and pick international logistics service providers with a stronger commitment to sustainability for settlement in local export parks. Second, government agencies should construct bridges to promote information transparency throughout the supply chain and enhance cooperation between export suppliers from developing nations and international logistics service providers (Weber et al, 2021). The government should also assist suppliers in identifying the requirements they must achieve in order to be approved as potential long-term partners by international logistics service providers, and promote knowledge sharing across the supply chain in order to address sustainability concerns.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Sustainability as a differentiated approach enables supply chain internal companies to remain competitive in the current business climate (Magazzino et al, 2022;Sun et al, 2022). Despite the growing interest of businesses in sustainable practices, multinational agri-food cold chains still face challenges in protecting the global environment (Weber et al, 2021). In fact, agri-food systems are relevant to all Sustainable Development Goals (SDGs), which makes their transition to holistic sustainability (ecological, economic, and social) imperative (Tochtrop et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, marketing that connects consumers through experience to a brand (Schmitt, 1999;Brakus et al, 2009) or places (Iaia et al, 2016), i.e., existential marketing, offers a promising approach to foster sustainable consumption behavior (Dettori, 2019;Eiseman & Jonsson, 2019). Researchers H. Weber, D. Lang, D. Wiek, and A. Loschelder (2021) indicated that experiential marketing tools, to varying degrees, indeed create connections from consumers to producers, thereby fostering sustainable consumption behavior. The findings can inform international food supply marketing efforts aimed at stimulating sustainable consumption.…”
Section: Social and Sustainable Marketing To Promote Socially Respons...mentioning
confidence: 99%